1998
DOI: 10.1097/00006123-199808000-00127
|View full text |Cite
|
Sign up to set email alerts
|

Combined Endovascular Stent Implantation and Endosaccular Coil Placement for the Treatment of a Wide-necked Vertebral Artery Aneurysm: Technical Case Report

Abstract: This report describes a case of a wide-necked intracranial artery aneurysm treated using a combination of endovascular stent implantation across an aneurysm neck and endosaccular coil placement to obliterate the aneurysm. The technique described provides another treatment to better manage the difficult entity of wide-necked intracranial aneurysms that may be unsuitable for clipping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(59 citation statements)
references
References 15 publications
2
53
0
3
Order By: Relevance
“…In our study, we observed that the mean VERs of the wide-and narrow-necked aneurysms were 27.5±23.1% and 29.4±26.6%, respectively, a difference that was not statistically significant (P>0.05) (Figure 4), when the wide-necked aneurysms were treated with intracranial vascular stents. Our results were consistent with those of previous studies (8,13,14,22,25), which determined that remodelling (14), intracranial vascular stenting (8,22), TriSpan neck-bridge devices (17) and threedimensional coils (25) improve both the coil packing within and the occlusion of wide-necked aneurysms. These results suggest that stent-assisted embolization increases both the density and the packing of wide-necked aneurysms, as well as the VERs of wide-necked aneurysms.…”
Section: Zhang Y Et Al: Ver Of Intraaneurysmal Embolizationsupporting
confidence: 93%
“…In our study, we observed that the mean VERs of the wide-and narrow-necked aneurysms were 27.5±23.1% and 29.4±26.6%, respectively, a difference that was not statistically significant (P>0.05) (Figure 4), when the wide-necked aneurysms were treated with intracranial vascular stents. Our results were consistent with those of previous studies (8,13,14,22,25), which determined that remodelling (14), intracranial vascular stenting (8,22), TriSpan neck-bridge devices (17) and threedimensional coils (25) improve both the coil packing within and the occlusion of wide-necked aneurysms. These results suggest that stent-assisted embolization increases both the density and the packing of wide-necked aneurysms, as well as the VERs of wide-necked aneurysms.…”
Section: Zhang Y Et Al: Ver Of Intraaneurysmal Embolizationsupporting
confidence: 93%
“…From then on, with improvements in microstent technology, more reports from various centers describing the experimental and clinical use of different stents for embolization assistance has reported good results in the literature. [7][8][9][10][11][12][13] Up till now, several literatures have demonstrated the technical feasibility, efficacy of treating complicated intracranial aneurysms. [14][15][16][17] The stent can provide a permanent scaffold across the aneurysm neck, which may prevent coil prolapse into the parent artery and allow for safer packing of the aneurysm with a denser coil mesh.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a stent also provides a matrix for endothelial growth. The luminal surface of the stent is covered by a layer of neointima and the segment from which the aneurysm arises is thereby remodeled 1,[17][18][19][20] . The approach to posterior circulation arteries by endovascular devices is quite direct and now there are available new, autoexpansible stents designed for intracranial use.…”
Section: Fig 2 Mra (A B) and Dsa (C D E) Shows Proximal (White Armentioning
confidence: 99%